The role of selected supplements and herbs in hyperprolactinemia therapy - a literature review - Anna Wiktorowska-Owczarek; Justyna Wolska; Alicja Wolska; Edward Kowalczyk; Agnieszka Wolska (Polish Pharmaceutical Society, 2021)
Hyperprolactinemia is a condition characterized by elevated prolactin levels in the blood. It is a prevalent endocrine disorder, typically observed among women and less often among men. The elevated level of prolactin may be caused by various physiological (including pregnancy, chronic stress, physical activity) and pathological conditions, among which the most commonly observed is a hormone-secreting (functional) pituitary adenoma - prolactinoma. The wide variety of symptoms associated with hyperprolactinemia is usually more pronounced in women, due to the significant impact of prolactin on the menstrual cycle. The secretion of prolactin, as in the case of other pituitary hormones, is strictly controlled by hypothalamic hormones and other specific hormones from the peripheral glands. The major hypothalamic factor responsible for the inhibition of both the synthesis and secretion of prolactin is dopamine. Based on the mechanism of action of this hormone, the treatment of hyperprolactinemia routinely begins with dopaminergic drugs. The main medications included in the group of dopamine agonists are bromocriptine, quinagolide, and cabergoline. In some cases of hyperprolactinemia, surgery may be necessary, usually as a form o therapy reserved for refractory and medication-intolerant patients. In addition to the treatment options mentioned above, the available literature indicates the beneficial effect of supplementation of certain vitamins and minerals as well as selected herbs on the normalization of prolactin levels. The beneficial effects are attributed, among others, to the preparations containing the extract of Vitex agnus-castus L. (chaste tree; chasteberry), Hordei fructus germinatus (so-called Mai-Ya, kind of herb germinating from barley), Mucuna pruriens (velvet bean) extract, vitamin B6 or zinc. This review aims to summarize the knowledge on the subject of the non-pharmacological treatment of hyperprolactinemia and to discuss the application of selected substances from the group of herbs, vitamins, and microelements.